The regulatory mapping of Kelantan state government / Nor Raihana Asmar Mohd Noor ...[et al.] - Mohd Noor, Nor Raihana Asmar; Zulkifli, Nursyahida; Tengku Zainal Mulok, Tengku Adida; Kamarul Zaman, Liziana; Fadzil, Faizal Haini; Yaacob, Norhayati (2020)
Nowadays, most of the governments in the world facing a challenging task of reviewing and updating laws and regulations that have been established for centuries. Most of these rules are outdated, obsolete, and sometimes overlapping and duplicative. The aim of this study is to reduce the number of unnecessary regulations and requirements. It is also to make the regulations are simpler, transparent and focuses on the legitimate regulatory process. To obtain a holistic view about this matter some personal interviews have been conducted against the respondents who are involved and responsible for the law enforcement. In fact some questionnaires had been distributed in order to collect primary and secondary data. This paper involved two (2) main phases: (i) gathering data and information regarding the existing regulations (ii) identifying any outdated, overlapped and duplicated regulations and need to be reviewed for improvement. 12 legal officers of all local authorities were interviewed, and face to face questionnaire surveys were distributed to state agencies officers to gain feedback on the existing regulations of Kelantan State Government. The findings indicate that there were existing regulations that have amended and repealed, however, there is a problem of inconsistent regulations, overlapped regulations and gazette but not implemented. This study benefits to the state government by producing a systematic regulatory mapping known as catalogue that can solve the problems of reviewing and updating existing regulations. These processes are important to make sure all the regulations are updated according to current changes. This study is regarded as the first attempt to investigate the existing regulations of Kelantan State Government